(untitled) (Linguostylistic Studies, 2019)
In recent years, researchers in the field of lexical systemology, cognitive, contrastive, and translational linguistics, intercultural communication have become increasingly interested in the issues of lacunarity. The concept of lacuna has transformed its content from the phenomena when a word of one language has no equivalent in another language (narrow understanding) to complex gaps in the interlingual and intercultural communication due to the national-specific features of culture and specific linguistic pictures of the communicants’ world (broad understanding of lacunae). Literary translation is a specific intercultural communicative situation. Mykhailo Stelmakh’s novel “Four Fords” and its translation into Russian is the case study for revealing lacunae and the ways of their elimination. Since an artistic text is a kind of a peculiar culturological model, which represents nationally specific features of verbal and nonverbal behavior of an ethnic group, the study of this text from the standpoint of lacunarity theory will enable its ethnic-psycholinguistic interpretation and optimize intercultural dialogue. What does not coincide in these languages and cultures requires interpretation, commenting, search for non-standard strategies for combining images of “one’s own” and “foreign” in order not only to understand but also to perceive the aesthetic charge of the original in the translator’s version adequately. All text lacunae, identified while comparing the original and the translation, tentatively fall into the categories of culturological and linguistic ones. The lacunae of the ethnocultural nature occur in case of national-specific realities, word-symbols, proper names, or precedent images of the Ukrainian folklore and literature. Linguistic gaps arise when a translator attempts to convey in target language words of some word-forming models or grammatical categories, author’s neologisms, emotional and evaluative vocabulary. The typological and genealogical similarity of the Slavic languages promotes transliteration as the most popular way of eliminating gaps, which may be accompanied by textual or line commentaries. A common practice is a descriptive way of interpreting non-equivalents or their lexical replacement (by a hyponym, hyperonym, or analogue). However, uncompensated gaps or translation losses are inevitable, even when the differences appear in similar linguistic pictures of the world.